The Effectiveness of E-Learning on Students in the Teaching of Children’s Literature Subject in Indonesian Language and Literature Study Program - Hutagalung, Trisnawati; Sari, Diah Eka; Wasilah, Atikah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study aimed at determining the effectiveness of learning using edmodo media on students in the course of teaching children's literature. The population in this study were all students of the Indonesian Language Education Study Program class of 2017 and who were sampled were 34 students. This research is using experimental method. The results of the study before using edmodo media in teaching children's literature got an average value of 71.2 with a standard deviation of 17.63 and a standard error of 3.0. After using edmodo media students get an average value of 87.6 with a standard deviation of 10.01 and a standard error of 1.71.